Quantitation of DNA adducts by stable isotope dilution mass spectrometry - Tretyakova, Natalia (2012)
Exposure to endogenous and exogenous chemicals can lead to the formation of structurally modified DNA bases (DNA adducts). If not repaired, these nucleobase lesions can cause polymerase errors during DNA replication, leading to heritable mutations potentially contributing to the development of cancer. Due to their critical role in cancer initiation, DNA adducts represent mechanism-based biomarkers of carcinogen exposure, and their quantitation is particularly useful for cancer risk assessment. DNA adducts are also valuable in mechanistic studies linking tumorigenic effects of environmental and industrial carcinogens to specific electrophilic species generated from their metabolism. While multiple experimental methodologies have been developed for DNA adduct analysis in biological samples – including immunoassay, HPLC, and (32)P-postlabeling – isotope dilution high performance liquid chromatography-electrospray ionization-tandem mass spectrometry (HPLC-ESI-MS/MS) generally has superior selectivity, sensitivity, accuracy, and reproducibility. As typical DNA adducts concentrations in biological samples are between 0.01 – 10 adducts per 10(8) normal nucleotides, ultrasensitive HPLC-ESI-MS/MS methodologies are required for their analysis. Recent developments in analytical separations and biological mass spectrometry – especially nanoflow HPLC, nanospray ionization MS, chip-MS, and high resolution MS – have pushed the limits of analytical HPLC-ESI-MS/MS methodologies for DNA adducts, allowing researchers to accurately measure their concentrations in biological samples from patients treated with DNA alkylating drugs and in populations exposed to carcinogens from urban air, drinking water, cooked food, alcohol, and cigarette smoke.